ANALISIS PENGARUH SUHU AIR CAMPUR TERHADAP KUAT TEKAN BETON - Eri Setia Romadhon; Imam Sudrajat (FTSP Universitas Jayabaya, 2021)
Concrete is the materials mixture between portland cement, water, soft aggregates, coarse aggregates with or without additif. Generally, Concrete mixture is using the water with the temperature between 20 – 35 0 C. This research is trying to know the effect from high temperature of water mixture to the concrete strength. Result from this research is the concrete strength with temperature of water mixture in 400C, 600C, and 700C showing that concrete with 3,7,and 14 days become 8,6%,15,7% and 13,1% .